2014
DOI: 10.5901/mjss.2014.v5n21p39
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Generations Y students’ Attitude towards Online Shopping

Abstract: Internet access grew exponentially in South Africa

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Whilst many studies have focused on Generation Y consumers and students specifically (Bevan-Dye, Garnett & De Klerk, 2012), there is scant research on buying behavior, social risk and their impact on retail store choice. Previous research has examined Generation Y students in various contexts by focusing on consumer shopping styles (Mandhlazi, Dhurup & Mafini, 2014), impulsive fashion apparel consumption (Dhurup, 2014), attitude towards online shopping (Makhitha, 2014), fashion consciousness behavior (Motale, Bevan-Dye & De Klerk, 2014) and innovation and risk-taking propensity (Koloba & May, 2014).Against this backdrop, there remains a vast scope for research in the apparel retail setting driven by a quest to have an ongoing understanding of the variables influencing purchase decisions among shoppers in South Africa (Mafini & Dhurup, 2015). Therefore, it can be noted that there is a paucity of empirical literature on perceived social risk, buying behavior and retail store choice decisions of Generation Y female students, thus the main objective of this study is to clear this gap in knowledge.…”
Section: Research Problem and Gapmentioning
confidence: 99%
“…Whilst many studies have focused on Generation Y consumers and students specifically (Bevan-Dye, Garnett & De Klerk, 2012), there is scant research on buying behavior, social risk and their impact on retail store choice. Previous research has examined Generation Y students in various contexts by focusing on consumer shopping styles (Mandhlazi, Dhurup & Mafini, 2014), impulsive fashion apparel consumption (Dhurup, 2014), attitude towards online shopping (Makhitha, 2014), fashion consciousness behavior (Motale, Bevan-Dye & De Klerk, 2014) and innovation and risk-taking propensity (Koloba & May, 2014).Against this backdrop, there remains a vast scope for research in the apparel retail setting driven by a quest to have an ongoing understanding of the variables influencing purchase decisions among shoppers in South Africa (Mafini & Dhurup, 2015). Therefore, it can be noted that there is a paucity of empirical literature on perceived social risk, buying behavior and retail store choice decisions of Generation Y female students, thus the main objective of this study is to clear this gap in knowledge.…”
Section: Research Problem and Gapmentioning
confidence: 99%
“…, enjoyment had a much stronger impact on attitude. Makhitha (2014), the perceptions towards online shopping did not diverge among Generation Y students in distinct age groups. It was discovered that the perceived comfort associated with shopping online affected the learners of Generation Y.…”
Section: Figure 1: Mobile Internet Usersmentioning
confidence: 75%
“…Existing studies also reported conflicting findings with some reporting age to have influence towards online shipping (Makhitha 2014;Makhitha et al 2019;Rudansky-Kloppers 2016), while others reported that age has no influence towards online shopping (Kim 2006).…”
Section: --mentioning
confidence: 99%